Cesare Zavattini’s poetics of objectivity - Borjan, Etami (Array, 2020)
Cesare Zavattini was an acclaimed neorealist screenwriter and a theorist of neorealism. He has played a pivotal role in the critical rethinking of the new postwar Italian cinema although many of his concepts were considered avant-garde for that period. He stood for a direct, spontaneous, and immediate cinema with real people and real events. Despite his desire to eliminate all that was fictional from his films, Zavattini’s concept of new realist cinema cannot simply be described as a documentary approach. He was not so much interested in making documentary films but in making documentary-like fictions. He believed in the potential of cinema to reach a wide audience and in its capacity to be aesthetically subversive. The aspiration for an avant-garde cinema that would reach the masses was a naïve attempt that was too radical for the Italian cinema at the time. Most of his ideas were not accepted in Italy, but he was admired by young filmmakers all over the world. Some of his ideas were realized a few decades later in the works of the famous cinéma vérité and independent avant-garde filmmakers. Throughout his career, Zavattini argued that cinema should be socially committed art. He believed that neorealist films should direct the viewer’s gaze toward specific social issues and voice a subjective judgment on it. In neorealist films, fictional style and documentary rhetoric make the illusion that the experience of characters stands for the experience of the audience.